The Effect of Gelatin Concentration on The Chemical and Organoleptic Characteristics of Nutmeg (Myristica Fragrans Houtt) Marshmallow - Malawat, Lisda Vina Wati; Sipahelut, Sophia Grace; Picauly, Priscillia (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2024)
Nutmeg (Myristica fragrans Houtt) is one of Indonesia's leading commodities. The parts of the nutmeg that have high economic value are the nutmeg seeds and mace, while the use of nutmeg pulp is still minimal, so it only becomes waste. Meanwhile, nutmeg flesh has the potential to be utilized because it contains various nutrients that are useful for health. One effort to increase the use of nutmeg pulp is to process it into marshmallows. In making marshmallows, one of the main basic ingredients is a gelling agent, such as gelatin. This research aims to determine the right gelatin concentration for making nutmeg marshmallows and which consumers prefer the most. The research design used was a completely randomized design with one factor, namely gelatin concentration consisting of four treatment levels, namely: 5%, 8%, 11% and 14%. The parameters observed included chemical tests (total phenol content, vitamin C content, total reducing sugar content, water content) and organoleptic tests (color, taste, aroma and texture). The results showed that the panelists preferred nutmeg marshmallow using a gelatin concentration of 14% compared to other treatments with characteristics including: total phenol content of 0.221 mg GAE/g, vitamin C content of 0.02 mg/100 g, total reducing sugar content of 4.28 %, water content 52.93%, slightly yellow color, slight nutmeg taste, nutmeg aroma, and chewy texture.